IMPLEMENTASI BSM PEMBAYARAN INSTITUSI MELALUI MANDIRI SYARIAH MOBILE DI UNIVERSITAS IBN KHALDUN BOGOR - Marlina, Asti; Maulida, Nadia (MONETER, 2020)
The development of digital banking is expanding and developing at any time to facilitate community activities and make time efficient. In implementing this, Bank Syariah Mandiri is present by providing BSM Institutional Payment (BPI) operational services that function as an institutional bill payment system that can be done through Bank Mandiri Syariah e-channels including Mandiri Syariah Mobile. One institution that cooperates in institutional payment services is the University. During the admission of new school year students and the change of new semesters, as well as the increasing case of Covid-19, banks and universities worked together on this service to reduce physical contact with many people in receiving tuition payments. Before implementation, the University needs to submit an application to the nearest branch office which is then forwarded to the head office so that it can be immediately implemented. Implementation of BSM Institutional Payments at the University of Ibn Khaldun Bogor is arguably still small, because students are still accustomed to manually paying by cash deposit.